ANALISA KEMAMPUAN PREDIKSI LABA DAN ARUS KAS DALAM MEMPREDIKSI ARUS KAS MASA MENDATANG - Aziz, lutfi (Jurnal Ilmu Akuntansi, 2023)
This study aims to determine the ability of earning and cash flow to predict future cash flow. Population in this study were companies listed on the Indonesia Stock Exchange in 2013-2020. In this study, the variable of earning use proxy for net income and variable of cash flow use proxy for operating or cash flow. The sample used in this study was banking companies listed on that Indonesia Stock Exchange in the period 2013-2020. Processing of data was done by doing classic assumption test first and then proceed to test the hypothesis. The hypothesis was tested using multiple linier regression. The result showed that earning and cash flow have an effect in predicting cash flow.